OPTIMIZATION OF PUBLIC TRANSPORT NETWORK IN THE UPPER ŠARIŠ REGION, SLOVAK REPUBLIC (Perner's Contacts, 2017)
This paper deals with public transport service in the Upper Šariš region, Slovakia. The paper is focused on both intraregional transport needs as well as connection of the region with an outside area – especially with the city of Prešov. The proposal takes into consideration current state of transport infrastructure, transport needs of inhabitants, present state of the transport service as well as selected operational aspects of proposed system.
Keywords: public transport; transport lines; optimization; integration